An Integrated Educational Audio-Visual Media Based Information Service Model in The Era of Industrial Revolution 4.0 for MTs Lab IKIP Al Washliyah Medan Students - Nurasyah; Rini Fadhillah Putri; Enny Fitriani; Johannes (International Journal of Educational Research Excellence (IJERE), 2023)
Current developments require all aspects of life, one of which is in the field of education, so that they can carry out transformational changes in the face of the industrial revolution 4.0. This situation is what made the government change the education system so that educators can improve their performance as teachers, including counseling teachers, so they can implement guidance and counseling services that are oriented towards the industrial revolution 4.0. This research aims to find out whether information services through audio-visual media can be effective in increasing understanding about education in the era of the industrial revolution 4.0 among Mts Lab IKIP Al Washliyah Medan students. This type of research is quantitative research with the population being 60 students in class VIII MTs Lab IKIP Al Washliyah Medan. Sampling used a random sampling technique which received as many as 30 students. The data collection technique in this research used a questionnaire. The questionnaire used in this research is an educational questionnaire in the era of the industrial revolution 4.0. with statistical data analysis. In this research, the data obtained shows that rcount is greater than rtable, namely 0.490 > 0.361 and has led to a better increase than before. This is known from the results of the t test which shows that tcount > ttable or 16.304 > 2.042. This shows that information services through audio-visual media can influence students' understanding of education in the era of the industrial revolution 4.0